2023
DOI: 10.3389/fenvs.2023.1079520
|View full text |Cite
|
Sign up to set email alerts
|

Varying performance of eight evapotranspiration products with aridity and vegetation greenness across the globe

Abstract: The wide application of the evapotranspiration (ET) products has deepened our understanding of the water, energy and carbon cycles, driving increased interest in regional and global assessments of their performance. However, evaluating ET products at a global scale with varying levels of dryness and vegetation greenness poses challenges due to a relative lack of reference data and potential water imbalance. Here, we evaluated the performance of eight state-of-the-art ET products derived from remote sensing, La… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 111 publications
0
6
0
Order By: Relevance
“…The results showed that diffuse radiation is more efficient than direct radiation in promoting the ET. This mainly because the increase in LUE, which can enhance the plant transpiration through their coupling in leaf stomata (B. Wang et al., 2023; H. Wang et al., 2023). Of course, the more uniform distribution of radiation induced by diffuse radiation also enhances the ETE (Chakraborty et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The results showed that diffuse radiation is more efficient than direct radiation in promoting the ET. This mainly because the increase in LUE, which can enhance the plant transpiration through their coupling in leaf stomata (B. Wang et al., 2023; H. Wang et al., 2023). Of course, the more uniform distribution of radiation induced by diffuse radiation also enhances the ETE (Chakraborty et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…To acquire the high‐quality data, the ground‐based data must meet the flowing criteria: corresponding QC data≥0.8; no precipitation. To investigate the response of vegetation to diffuse radiation, we only analyze the data during the growing seasons, which are mainly distributed to May‐September in the Northern Hemisphere and September‐March in the Southern Hemisphere (B. Wang et al., 2023; H. Wang et al., 2023).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations